Molecular cloning of epididymal and seminal vesicular transcripts encoding a semenogelin-related protein. - Lilja, H (1992)
Freshly ejaculated human semen has the appearance of a loose gel in which the predominant structural protein components are the seminal vesicle-secreted semenogelins (Sg). The primary structure of the 439-residue SgI has previously been obtained by cDNA cloning. This cDNA cross-hybridizes to a larger transcript coding for a second secretory protein, SgII. Here we report the almost complete structure of a precursor of SgII established by lambda gt11 clones isolated from epididymal and seminal vesicular cDNA libraries. The deduced amino acid sequence of the 559-residue mature protein has a molecular weight of 62,931 but an increase in weight may be provided by asparagine-linked oligosaccharide attachment at residue 249. SgII, which has 78% overall identity with SgI, contains eight 60-residue regions that display conspicuous internal sequence similarity, whereas SgI only contains six of these regions. The SgII structure is translated from an open reading frame in a polyadenylylated 2.4-kilobase transcript. The message is abundant in the seminal vesicles but rare in the epididymis.